The cultural customs of Afghanistan muslims during pregnancy, childbirth and postpartum period: based on the results of the interviews - Merits, Marika; Sildver, Kaire; Bartels, Irena; Meejärv, Kirlin (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
The thesis is a part of Tallinn Health Care College, Department of Midwifery research: The cultural customs of Afghanistan muslims during pregnancy, childbirth and postpartum period: based on the results of the interviews during professional training of Afghan midwives in Estonia in 2015. 53% of all the war refugees around the world headed to Europe in 2015, including the refugees from Afghanistan with Islam as the majority religion. According to Statistics Estonia, the immigration to Estonia has also increased in recent years. 27% of the migrants heading to Estonia were from outside of the European Union in 2015. It is important to know the culture of Afghanistan and similar countries, and to understand the individual needs of the migrants from these countries in order to provide them with high-quality health care.